Exploring Islamic Teachers’ Speech Acts in the Classroom at Private Islamic Junior High School in Rokan Hulu Riau - Miski, Cut Raudhatul; Erni, Sukma; Roza, Ellya; Afrida, Afrida (Universitas Islam Negeri Sultan Syarif Kasim Riau, 2024)
Teachers’ ability to communicate lessons in the classroom is necessary needed to create meaningful teaching and learning process. The selection of words, how the words arranged and how they are uttered determine whether the class run effectively active or vice versa. Even, the nominal of utterances of teacher state how the class is conducted. The excessive proportion of the teacher's speech will actually make the class inactive and the teacher will have difficulty assessing the extent to which students understand the material presented. Barnes (2008) in Groves and Bull (2014) mentioned that teacher talk or teachers' speech in the classroom has an important role in improving and developing students' knowledge skills. This research was piloted to explore what speech acts expressed by the Islamic teachers in their classroom as it ended up to determine how the class directed. The research is qualitative design by taking one Islamic teacher of Private Islamic Junior High School in Rokan Hulu. The result mentions that the most dominant speech acts is the ordering of directive speech act. In this case, teacher often ordered students to accomplish their group discussion and present the result in front of the class. while the lack of productive questions on the stage of interactive and reflection lead to less of students’ critical thinking. For the next research, it is suggested to have more participants and use supplementary instruments to enrich the data.